A systematic review and meta‐analysis of studies that have evaluated the role of mitochondrial function and iron metabolism in frailty. Issue 6 (9th July 2021) - Tomkova, Kristina; Pathak, Suraj; Abbasciano, Riccardo; Wozniak, Marcin; Murphy, Gavin J.
Abstract: Frailty is a condition of global impairment due to depletion of physiological reserves. However, the underlying biological mechanisms are poorly understood. The aims of the current study were to identify the differences in mitochondrial function and iron metabolism between frail and nonfrail populations, and to investigate the contribution of different methodological approaches to the results. Searches were performed, using five online databases up to November 2019. Studies reporting measurements of mitochondrial function or iron metabolism in frail and nonfrail subjects or subjects with and without sarcopenia, were included. Pooled effect estimates were expressed as Standardized Mean Differences. Heterogeneity, expressed as I 2, was explored using regression analyses. In total, 107 studies, reporting 75 measures of mitochondrial function or iron metabolism, using six different experimental approaches, in three species were identified. Significant decreases in measures of oxygen consumption were observed for frail humans but not in animal models. Conversely, no differences between frail and nonfrail humans were observed for apoptosis and autophagy, in contrast to animal models. The most significant effect of the type of frailty assessment was observed for respiratory chain complexes where only subjects categorized as frail by the Fried Frailty Index showed a significant decrease in activity. We identified iron metabolism in frailty as an important knowledge gap, highlighted the need of consistent frailty diagnostic tools, and pointed out the limited translational potential of animal models. Inconsistency between studies evaluating the molecular mechanisms underlying frailty may present a barrier to the development of effective therapies.